KEPUASAN KONSUMEN DALAM BERBELANJA MELALUI E-TAILING UNTUK MENINGKATKAN LOYALITAS KONSUMEN - Nani Agustina (Paradigma, 2011)
Technological advances developed in all areas without exception the development of SMEs are ready to compete with large corporations sector, where start utilizing technology to harness the internet as a means to marketing products to be promoted and meningkalkan conventional media. Utilizing online shopping is by means of social network or by using a company profile in the absence of interaction between the seller and the buyer. With variable support and service, content quality and trust as to whether to create the level of customer satisfaction and e-commerce will generate customer loyalty for online shopping repeatedly. In this study measuring how much the influence of these variables are related. Use measurement to process data using SPSS 16 for measuring reliability and validity, while the indicator to measure the influence between using AMOS 7.0. Keywords : Satisfaction, Loyalty, E-tailing